2019
DOI: 10.3233/wor-192927
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapists with work-related musculoskeletal disorders in the State of Kuwait: A comparison across countries and health care professions

Abstract: BACKGROUND: In the US, as the demands for rehabilitation services increase, work-related musculoskeletal disorders (WMSDs) have increased among rehabilitation practitioners. This trend has been noticed among physical therapists (PTs) in the State of Kuwait. OBJECTIVE: The purpose of this study was to determine the prevalence and risk factors associated with WMSDs among PTs in Kuwait over a 12-month period. In addition, the result compared across countries and health care professions. METHODS: A descriptive cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Physiotherapists are exposed to the overloading of the musculoskeletal system associated with the non-ergonomic position (19). Modern methods also require the strength of the whole body and using the force of the hands to get the proper function of the patient (19,20). One-year prevalence of WMSD among physiotherapists ranges from 28 to 96% (13).…”
Section: Wmsd Among Physiotherapistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiotherapists are exposed to the overloading of the musculoskeletal system associated with the non-ergonomic position (19). Modern methods also require the strength of the whole body and using the force of the hands to get the proper function of the patient (19,20). One-year prevalence of WMSD among physiotherapists ranges from 28 to 96% (13).…”
Section: Wmsd Among Physiotherapistsmentioning
confidence: 99%
“…One-year prevalence of WMSD among physiotherapists ranges from 28 to 96% (13). Low back pain is the most common problem of physiotherapists (11,(13)(14)(15)17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). For the lower back area, the 1-year prevalence is 6.6-83%, mostly due to repeated lifting and transferring, twisting, and bending or standing for a long time (13,23).…”
Section: Wmsd Among Physiotherapistsmentioning
confidence: 99%
“…In physical therapists, wrist, hand, and finger pain is mostly related to their work [17]. More than 20% of physical therapists experience wrist and hand injuries, which limits their ability to perform manual therapy techniques [18]. Therefore, treatment tools are being developed that can protect the wrists and hand of physical therapists and provide effective treatment for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since the rehabilitation professionals play a primary role in various medical procedures, such as conducting physical examinations of patients, caregiving, providing hygiene, positioning, monitoring vital functions, taking blood samples, applying medications, implement of physical therapy modalities, planning and manufacturing orthotic materials, preparation medical documents and reports; they remain in fixed and sometimes non-optimal positions of the body, which can lead to diseases of the musculoskeletal system for a long time. There are few studies in literature which determines the musculokeletal complaints in rehabilitation professionals (2,3,4). In a study by Islam et al (2) it was revealed that ninety-five percent of the participants complained of work related pain and most of the participants reported pain in the lower back (n=84) followed by upper back (n=71) and neck (n=66) .…”
Section: Introductionmentioning
confidence: 99%